Hubungan Antara Job Demand Terhadap Kinerja Karyawan Melalui Burnout - Anesia Mulya Diana; Agus Frianto (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2020)
This study aims to determine job demand, employee performance, and burnout. This study uses a literature study research method with a number of journals from previous researchers, and gets results that demand for work has a positive effect on burnout. This shows that job demand can cause fatigue with different initial syndromes according to the level of job demand received by each individual. Job requests have a negative effect on employee performance. The demand for work experienced can trigger individuals to implement their own potential. If job demands are not managed properly, it can worsen performance, so skills and ability training is needed to improve employee performance. Burnout has a negative effect on performance. Burnout experienced can be controlled because each individual has the ability or competence. Job demand has a positive effect on employee performance through fatigue. This means that burnout can mediate the direct effect of job demand on employee performance. Limitations in this study are only the literature review so it is necessary to conduct deeper research and analysis related to the variables of job demand, employee performance and fatigue. Looking at the differences and limitations in the results of previous studies, it is possible to examine and conduct further research on the relationship between these variables in future studies. The next research was conducted quantitative research with primary data sources through questionnaires and direct interviews, so as to find out how the relationship between work demand and employee performance through burnout.